Was Marcin Siennik the translator of “Fortunatus”? An Attempt to Identify the Author of an Anonymous Polish Translation from the Second Half of the 16th Century - Semko, Franciszek; Wierzbicka-Trwoga, Krystyna (Melusine. Old Literature and Culture, 2025)
The aim of our article is to verify the thesis of the German Slavist Jurij Striedter, who in 1960 undertook an attempt to identify the author of the Polish translation of “Fortunatus”, a popular German novel from the early 16th century. The researcher indicated three fragments containing botanical vocabulary added to the basis of the translation. Upon partial analysis of the plant and animal terms in “Fortunat” and their similarity to Marcin Siennik’s “Herbarz” (“Herbarium”), he concluded that Siennik could have been the translator of the work. The authors of the article examine Striedter’s thesis by referring to current knowledge of 16th-century Polish botanical vocabulary and analysing three more passages from “Fortunat”, which give the names of plant species and liquors also described in Siennik’s “Herbarz”.